A randomized controlled trial of physical activity, dietary habit, and distress management with the Leadership and Coaching for Health (LEACH) program for disease-free cancer survivors - Young Ho Yun; Young Ae Kim; Myung Kyung Lee; Jin Ah Sim; Byung-Ho Nam; Sohee Kim; Eun Sook Lee; Dong-Young Noh; Jae-Young Lim; Sung Kim; Si-Young Kim; Chi-Heum Cho; et al. (BMC Cancer, 2017)
Abstract Background We aimed to evaluate the potential benefits of the Leadership and Coaching for Health (LEACH) program on physical activity (PA), dietary habits, and distress management in cancer survivors. Methods We randomly assigned 248 cancer survivors with an allocation ratio of two-to-one to the LEACH program (LP) group, coached by long-term survivors, or the usual care (UC) group. At baseline, 3, 6, and 12 months, we used PA scores, the intake of vegetables and fruits (VF), and the Post Traumatic Growth Inventory (PTGI) as primary outcomes and, for secondary outcomes, the Ten Rules for Highly Effective Health Behavior adhered to and quality of life (QOL), the Hospital Anxiety and Depression Scale (HADS), and the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30). Results For primary outcomes, the two groups did not significantly differ in PA scores or VF intake but differed marginally in PTGI. For secondary outcomes, the LP group showed a significantly greater improvement in the HADS anxiety score, the social functioning score, and the appetite loss and financial difficulties scores of the EORTC QLQ-C30 scales from baseline to 3 months. From baseline to 12 months, the LP group showed a significantly greater decrease in the EORTC QLQ-C30 fatigue score and a significantly greater increase in the number of the Ten Rules for Highly Effective Health Behavior. Conclusion Our findings indicate that the LEACH program, coached by long-term survivors, can provide effective management of the QOL of cancer survivors but not of their PA or dietary habits. Trial registration Clinical trial information can be found for the following: NCT01527409 (the date when the trial was registered: February 2012).